Electrophysiological characteristics of pressure overload-induced cardiac hypertrophy and its influence on ventricular arrhythmias. - Xiaowei Chen; Mu Qin; Weifeng Jiang; Yu Zhang; Xu Liu (PLoS ONE)
Objective To explore the cardiac electrophysiological characteristics of cardiac hypertrophy and its influence on the occurrence of ventricular tachyarrhythmias. Methods Adult C57BL6 mice were randomly divided into a surgery group and a control group. Thoracic aortic constriction was performed on mice in the surgery group, and cardiac anatomical and ultrasonic evaluations were performed to confirm the success of the cardiac hypertrophy model 4 weeks after the operation. Using the Langendorff method of isolated heart perfusion, monophasic action potentials (MAPs) and the effective refractory period (ERP) at different parts of the heart (including the epi- and endo-myocardium of the left and right ventricles) were measured, and the induction rate of ventricular tachyarrhythmias was observed under programmed electrical stimulus (PES) and burst stimulus. Whole-cell patch-clamp was used to obtain the I-V characteristics of voltage-gated potassium channels in cardiomyocytes of different parts of the heart (including the epi- and endo-myocardium of the left and right ventricles) as well as the channels' properties of steady-state inactivation and recovery from inactivation. Results The ratio of heart weight to body weight and the ratio of left ventricular weight to body weight in the surgery group were significantly higher than those in the control group (P < 0.05). Ultrasonic evaluation revealed that both interventricular septal diameter (IVSD) and left ventricle posterior wall diameter (LVPWD) in the surgery group were significantly larger than those in the control group (P < 0.05). Under PES and burst stimuli, the induction rates of arrhythmias in the surgery group significantly increased, reaching 41.2% and 23.5%, respectively. Both the QT interval and action potential duration (APD) in the surgery group were significantly longer than in the control group (P<0.01), and the changes showed obvious spatial heterogeneity. Whole-cell patch-clamp recordings demonstrated that the surgery group had significantly lower potassium current densities (IPeak, Ito, IKur, Iss, and IK1) at different parts of the heart than the control group (P < 0.01), and there were significant differences in the half-inactivation voltage (V1/2) and the inactivation-recovery time constant (τ) of Ito and IKur at different parts of the heart (P < 0.01) between the surgery group and the control group. In addition, the surgery group had significantly lower densities of IPeak, Ito, and IKur in cells of the endo-myocardium (P < 0.05), and the changes showed obvious spatial heterogeneity. Conclusion Changes in the current density and function of potassium channels contributed to irregular repolarization in cardiac hypertrophy, and the spatially heterogeneous changes of the channels may increase the occurrence of ventricular arrhythmias that accompany cardiac hypertrophy.